National agendas priorities and strategies for change in Asean (Association For South East Asian)countries. - Anis, Shawaluddin (1995)
In spite of the economic dynamism of the ASEAN countries (Malaysia, Indonesia, Singapore, Thailand, Philippines and Brunei) in the last two decades poverty has been a threat to economic development. Poverty which has been described in the literature with more than one dimension: the dimensions of time, distribution, and attitudes have been of great concern to policy makers and scholars alike.